The iPosyandu Application for Midwives as Learning Media in Continuity Midwifery Care Training Curriculum - Susanti, Ari Indra; Mohammad Ali; Asep Herry Hernawan; Fedri Ruluwedrata Rinawan (Journal of Education Technology, 2022)
Currently, village midwives are experiencing an increased workload because there are more and more health service programs, so they cannot provide optimal sustainable midwifery care. This study analyzes the relationship between iPosyandu application-based training media and training materials for continuing midwifery care and learning evaluation. This type of research is analytical research with a cross-sectional research design. The research subjects were 110 people. Data was collected by providing the village midwife with an online questionnaire (google form). Univariate data were processed and analyzed to determine all research variables' mean and standard deviation values. Bivariate data analysis with Pearson test due to the type of numeric data. The study found no correlation between the components of the training curriculum (including training materials, learning media, and learning evaluation) and continuing midwifery care competencies. However, there is a significant correlation between training materials and learning media. In addition, a significant correlation was found between learning evaluation and learning media. It was concluded that the components of the training curriculum were interrelated so that the iPosyandu application could be used as a training medium for all competencies in training. This research implies that midwives can use the iPosyandu application as a learning medium that makes it easy to access training materials, thereby saving training costs for midwives as training participants and organizers.